Derive Program Implementation in Mathematics (The Math Learning of State Polytechnic Malang) - Dewi, Mutia Lina (UI Scholars Hub, 2017)
A lot of students have difficulty in Math. Every semester there are always students who get D or E for Math. It makes low average score and the students who get E or IP<2,00 are dropped out. The lecturer must have many methods to help them. The Derive Program of Window software can help the students to increase their motivation. The functions of Derive Program are like a calculator. The subjects depend on the needs of the Department. For Civil Engineering needs the subject of Matrix, Determinant, Equation, Graphs, Derivative, and Integral. The result of average Math score of Derive Program is better than the Theory. The motivation of students has increased and students have enjoyed, have fun and spirit, and are more interested to solve problems in Math.